1992
DOI: 10.1128/aac.36.7.1478
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of nonoxynol 9 on HeLa 229 cells and primary monkey cervical epithelial cells infected with Chlamydia trachomatis

Abstract: Nonoxynol 9 (non-9) is the active ingredient in a wide variety of vaginal contraceptive preparations. The manufacturer recommendation for optimal contraceptive practice is repeated application every 6 h. We studied the in vitro activity of non-9 against Chlamydia trachomatis (E/UW-5/Cx) and its toxicity against HeLa 229 cells and monkey cervical epithelial cells. With a contact time of 6 h, non-9 was toxic to HeLa cells at concentrations of 50 ,ug/ml or greater and to monkey cervical cells at 100 ,ug/ml or gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…Several compounds such as chlorhexidine gluconate (Lampe et al 1998), nonoxynol-9 (Benes andMcCormack 1985;Kelly et al 1985;Patton et al 1992), protegrins and defensins (Yasin et al 1996) have in vitro inhibitory effects on C. trachomatis, and their topical application for clinical usage have been suggested. Clinical application of ozone water in chlamydial infections would involve repeated washing.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds such as chlorhexidine gluconate (Lampe et al 1998), nonoxynol-9 (Benes andMcCormack 1985;Kelly et al 1985;Patton et al 1992), protegrins and defensins (Yasin et al 1996) have in vitro inhibitory effects on C. trachomatis, and their topical application for clinical usage have been suggested. Clinical application of ozone water in chlamydial infections would involve repeated washing.…”
Section: Discussionmentioning
confidence: 99%
“…11,26 The potential for cumulative damage should now be considered an important assessment factor, particularly for membrane-active compounds. In contrast, cells were observed to be relatively resistant during the first 24 hours of exposure.…”
Section: N-9 Cytotoxicitymentioning
confidence: 99%
“…3 N-9 has been used at concentrations between 2% and 12% as the active component of spermicides for more than a quarter of a century. [6][7][8][9][10][11][12] Consequently, its potential for reducing the transmission of STIs had been suggested long before the onset of the HIV epidemic. 4,5 Early studies indicated that N-9 was active against a range of microbes and/or pathogens in vitro, including herpes simplex virus (HSV), cytomegalovirus, Neisseria gonorrhoeae, Trichomonas vaginalis, Treponema pallidum, Gardnerella vaginalis, Bacteroides, and Chlamydia trachomatis.…”
mentioning
confidence: 99%
“…Initial attempts to develop topical microbicides focused on commercially available spermicides containing nonoxynol‐9 (N‐9). N‐9 has been shown to be active in vitro against STI pathogens, including human immunodeficiency virus (HIV), herpes simplex virus (HSV), and Chlamydia trachomatis [3–7]. Given their long history of clinical use, commercial spermicides containing N‐9 appeared to be excellent topical microbicide candidates.…”
Section: Introductionmentioning
confidence: 99%